"ASR expansion, expansive pressure and cracking in concrete prisms under various degrees of restraint" by Hiroyuki Kagimoto, Yukihiro Yasuda, Mitsunori Kawamura. (January 2016) - Hansen, S.G.; Skou, D.
Abstract: Discussion of restraint definition in experimental setups for ASR expansion tests.